A dual strategy account of individual differences in information processing in contingency judgments. Issue 4 (19th May 2021) - Béghin, Gaëtan; Gagnon-St-Pierre, Émilie; Markovits, Henry
ABSTRACT: The dual strategy model of reasoning suggests that people can either use a Statistical or a Counterexample strategy to process information. Previous studies on contingency learning have shown a sufficiency bias: people give more importance to events where the potential cause is present (sufficiency) rather than events where the potential cause is absent (necessity). We examine the hypothesis that strategy use predicts individual differences in use of sufficiency information in contingency judgements. Study 1 used an active learning contingency task. Results showed that Statistical reasoners were more influenced by sufficiency information than Counterexample reasoners. Study 2 used a passive learning contingency task, where sufficiency was constant and only necessity information (based on outcomes when the potential cause was absent) was varied. Results showed that only Counterexample reasoners were sensitive to necessity information. These results demonstrate that strategy use is correlated with individual differences in information processing in contingency learning.